Association between e-cigarette use, physical activity and cardiorespiratory fitness: protocol for a systematic review - Javad Heshmati; Hassan Mir; Hayley Thode (BMJ Open, 2025)
Introduction Despite the rise in popularity of e-cigarette smoking or ‘vaping’, its long-term health consequences are still being investigated. In particular, it is unclear what impact e-cigarette use has on aerobic performance and exercise capacity. This information has important implications both for tobacco smokers as a harm reduction approach, and youth and young adults who are increasingly turning to e-cigarettes recreationally. Thus, this review aims to systematically evaluate the literature surrounding the effects of regular e-cigarette use on markers of cardiorespiratory fitness and physical activity.Methods and analysis This protocol follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines. A systematic search was undertaken in October 2024, using the defined population, intervention, comparison, outcomes, study time framework to identify all relevant articles. Studies will be eligible if they include individuals who use e-cigarette products, assess regular e-cigarette use as an exposure, compare to a group of non-users and report outcomes related to measures of cardiorespiratory fitness (eg, VO2max, 6 min walk test) or physical activity (eg, sport participation, meeting weekly physical activity guidelines), regardless of study duration. Searched databases will include PubMed/Medline, Cochrane Library and Embase, with no restriction to date or language of publication. Two reviewers will carry out the title and abstract screening, full text review and data extraction. Risk of bias will be assessed using the Newcastle-Ottawa Scale for non-randomised studies and the Cochrane Risk of Bias Tool (v2) for randomised studies. Study heterogeneity will be assessed using the Q and I2 statistic tests. Efforts will be made to conduct a meta-analysis if sufficient data and homogeneity are present. Otherwise, a narrative synthesis will be conducted, focusing on common themes, subgroups and sources of variability.Ethics and dissemination Ethics approval is not required for this review of previously published or presented data. The results of the review will be disseminated via conference presentations and peer-reviewed publication. Moreover, results of this review may inform public health recommendations and identify areas in the field where further research is needed.PROSPERO registration number CRD420250589685.